Pengembangan Jobsheet Berbasis Project Technopreneurship pada Mata Kuliah Instalasi Listrik Industri - Nadilla Febrialita; Elfizon Elfizon (Jurnal Pendidikan Teknik Elektro, 2021)
Industrial electrical installation practice is a course in the electrical engineering department of Padang State University that must be taken by students. The learning process in the Industrial Electrical Installation course has not fostered the spirit of Technopreneurship because it still prioritizes the achievement of competence in the industry. The existing job sheets are good but have not been able to bring students to the level of entrepreneurship. Where the entrepreneurial spirit is very lacking for students which will later be beneficial for students who want to develop technopreneurship-based jobsheets. For this reason, this study aims to produce a valid, practical, and effective technorpreneurship project-based job sheet model. The research method used is the Research and Development method with a 4D model. The subject of the research is a practicum jobsheet for students majoring in Electrical Engineering, Faculty of Engineering, UNP for the academic year 2021. Based on the results of the study, the validity of the jobsheet model based on the technopreneurship project was obtained from 3 validators (material expert validators and media expert validators) in the Valid category. Practical test with respondents of Industrial Electrical Installation Practice Course Lecturers by stating that the industrial electrical installation practice worksheet based on technopreneurship projects is practical. The effectiveness test with student respondents was limited by stating that the industrial electrical installation practice worksheet based on technopreneurship projects was effective. From the research data above, it can be concluded that the industrial electrical installation practice worksheet model is valid, practical, and effectively used for industrial electrical installation practice lectures.